factorise x(x-a)-y(y-a)

Asked by Jayasree C | 29th Jul, 2012, 03:44: PM

Expert Answer:

Answer : Given :  x(x-a)-y(y-a)
To factorise the above.
 
Let f(x) = x(x-a)-y(y-a)
=> f(x) = x- ax - y2+ ay
=> f(x) = x- y - ax + ay    { rearranging the quatities } 
=> f(x) =  ( (x - y)(x+y) )  - a ( x -y )    { using a2 - b2 = (a+b) (a-b) }
 
Take (x - y) common  , we get 
=> f(x) = (x - y) (x + y - a ) Answer

Answered by  | 30th Jul, 2012, 02:14: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.